Tentorial Incision vs. Retraction of the Tentorial Edge during the Subtemporal Approach: Anatomical Comparison in Cadaveric Dissections and Retrospective Clinical Case Series - Archavlis, E.; Serrano, L.; Ringel, F.; Kantelhardt, S. R. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective The aim of this study was to compare tentorial incision (group A) versus retraction and tack up suture (group B) of the tentorial edge during the subtemporal approach for surgery in the high basilar region.Design 24 cadaveric dissections and 4 clinical cases of aneurysms of the high basilar region are presented. Assessment included visibility and operability afforded by either tentorial incision creating a dural flap (group A) or retraction of the tentorial edge and tethering with a suture (group B). Four patients, two with superior cerebellar artery aneurysms and two with proximal posterior cerebral artery aneurysms were treated with each approach.Results In the quantitative evaluations, we found no significant difference in the exposure of the posterior cerebral, superior cerebellar, and perforant arteries as well as surgical working area provided by either approach. However, tentorial incision allowed a significantly greater exposure of the basilar artery and the fourth cranial nerve (both p < 0.001). Concerning operability, tentorial incision provided no objective advantage for direct clipping of the high basilar region (groups A vs. B, p > 0.05). Subjectively, clipping of the high basilar segment was feasible using tentorial tethering only.Conclusion Retraction of the free edge of the tentorium downward by tethering with a suture is simple and fast method for exposure of aneurysms in the high basilar region when the pathology does not require a proximal control. In our data the rather more invasive and time consuming tentorial incision provided an additional objectified advantage only for placement of a proximal temporary clip.
Keywords: tentorial incision; tentorial retraction; tentorial tethering; subtemporal approach; high basilar aneurysm